2023
DOI: 10.3390/pathogens12070939
|View full text |Cite
|
Sign up to set email alerts
|

Neglected Zoonotic Diseases: Advances in the Development of Cell-Penetrating and Antimicrobial Peptides against Leishmaniosis and Chagas Disease

Sara M. Robledo,
Silvia Pérez-Silanes,
Celia Fernández-Rubio
et al.

Abstract: In 2020, the WHO established the road map for neglected tropical diseases 2021–2030, which aims to control and eradicate 20 diseases, including leishmaniosis and Chagas disease. In addition, since 2015, the WHO has been developing a Global Action Plan on Antimicrobial Resistance. In this context, the achievement of innovative strategies as an alternative to replace conventional therapies is a first-order socio-sanitary priority, especially regarding endemic zoonoses in poor regions, such as those caused by Try… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 205 publications
0
11
0
Order By: Relevance
“…CL-prolixicin not only reduced the reproduction and survival of T. cruzi , it also severely impaired its motility 51 , 52 . Antiparasitic activity of various AMPs, such as BatxC, cecropin, crotalicidin, defensin a1138, dermaseptins, and mellitin, against T. cruzi has previously been demonstrated under laboratory conditions 16 , 31 , 52 54 . Results obtained in laboratory experiments suggested that T. cruzi may survive in the bed bugs’ midgut but is killed if it enters the hemocoel 27 , 29 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CL-prolixicin not only reduced the reproduction and survival of T. cruzi , it also severely impaired its motility 51 , 52 . Antiparasitic activity of various AMPs, such as BatxC, cecropin, crotalicidin, defensin a1138, dermaseptins, and mellitin, against T. cruzi has previously been demonstrated under laboratory conditions 16 , 31 , 52 54 . Results obtained in laboratory experiments suggested that T. cruzi may survive in the bed bugs’ midgut but is killed if it enters the hemocoel 27 , 29 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been hypothesized that some components of the bed bugs’ innate immune responses, including AMPs, prevent the establishment and replication of pathogens and their transmission to new hosts. Moreover, since 2020, the World Health Organization has assigned key roles to AMPs in the fight against neglected tropical diseases, including Chagas disease 30 , 31 .…”
Section: Introductionmentioning
confidence: 99%
“…Due to their direct anti-microbial killing activity and significant role in innate immunity, AMPs represent a promising alternative to existing antibiotics in the treatment and prevention of microbial infections [ 292 ]. To date, more than 2000 AMPs have been discovered, and many exhibit broad-spectrum anti-bacterial, anti-viral, and anti-parasitic activity [ 294 ]. Research on the potential application of AMPs’ structural and natural analogs in the fight against NTDs is ongoing [ 292 ].…”
Section: Peptide Targeting For Leishmaniasis and Chagas Disease Thera...mentioning
confidence: 99%
“…The primary mechanism by Ih AIPs inhibit parasItic infection is by binding to and rupturing the plasma membrane of the parasites [ 294 , 295 ]. Most of these peptides are cationic–amphipathic, exhibiting two main mechanisms of action: direct lysis and modulating the immune system [ 289 ].…”
Section: Peptide Targeting For Leishmaniasis and Chagas Disease Thera...mentioning
confidence: 99%
See 1 more Smart Citation